2012
DOI: 10.1080/14786419.2012.668691
|View full text |Cite
|
Sign up to set email alerts
|

Comparative chemical composition and in vitro antioxidant activities of essential oil isolated from the leaves of Cinnamomum tamala and Pimenta dioica

Abstract: Cinnamomum tamala Nees and Eberm (tejpat) and Pimenta dioica (L.) Merr (pimento) leaves are commonly used for flavouring food and widely used in pharmaceutical preparations because of their hypoglycemic, carminative and stimulant properties. In this study, we compared the chemical composition and antioxidant activities of tejpat and pimento essential oils by employing various in vitro methods. GC and GC-MS analyses were done to find out the chemical composition, and the main constituent identified in tejpat an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…The lower IC 50 value gives a better protective action and shows a strong ability of the EO to act as DPPH scavenger and vice versa that were required to achieve 50% scavenging reaction (Ray et al, ). This formation of reduced DPPH‐H also depends on the presence of eugenol compound (Amma, Rani, Sasidharan, & Sreekumar, ) which was found in BLEO. From this study, the AA of fresh BLEO was expressed with a low IC 50 value, indicating that the oil acts as a strong and effective DPPH.…”
Section: Resultsmentioning
confidence: 91%
“…The lower IC 50 value gives a better protective action and shows a strong ability of the EO to act as DPPH scavenger and vice versa that were required to achieve 50% scavenging reaction (Ray et al, ). This formation of reduced DPPH‐H also depends on the presence of eugenol compound (Amma, Rani, Sasidharan, & Sreekumar, ) which was found in BLEO. From this study, the AA of fresh BLEO was expressed with a low IC 50 value, indicating that the oil acts as a strong and effective DPPH.…”
Section: Resultsmentioning
confidence: 91%
“…This essential oil has been studied for different applications. The antioxidant potential of allspice oil was evaluated by many researchers and all of them have found that this essential oil has good antioxidant activity and can be utilized as a natural antioxidant [7,8,12,13]. In more specific applications the allspice essential oil was used as an anti-inflammatory [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, since mankind has chosen to consume natural products the allspice essential oil is used massively in food, pharmaceutical, and perfume industries [9]. Due to its high content of eugenol, methyl eugenol, myrcene, and caryophyllene [7,10] The high levels of eugenol contained in clove essential oil give it strong biological activity and antimicrobial activity. This phenolic compound can denature proteins and reacts with cell membrane phospholipids changing their permeability [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, leaves of this plant are effective in diabetic rats have antioxidants as well as have hypoglycemic anti-inflammatory and immunomodulation properties. [7][8][9][10] Recent studies shows that the leaf extracts of the plant have antidiabetic and antioxidant activities in streptozotocin (stz) treated diabetic rats and the bark was reported to have anti-diabetic activity by using α-amylase inhibition assay. 11,12 The present study focuses on the antidiabetic activities of the leaf extracts of C. tamala which are usually used in South-Asian cooking and sample was collected locally.…”
Section: Introductionmentioning
confidence: 99%